Soft Tissue Changes after Orthognathic Surgery: A Study - Upadhyaya, Chandran; Baliga, Mohan; Shetty, Premalatha (Orthodontic Journal of Nepal, 2011)
Aim and objective: The main aim and objectives of this study was to determine the changes in the facial soft tissue profile following orthognathic surgery, to evaluate eventual treatment effects on stability of facial aesthetics and degree of predictability of these changes. Materials and method: 15 numbers of patients underwent with le fort I, anterior maxillary osteotomy, genioplasty and bimaxillary surgery. The alar base cinch suture and the V-Y closure techniques were used in each maxillary procedure. The criteria applied included an average follow-up of 6 months post-operatively. Results: In this study preoperative and postoperative cephalometric tracing were compared to analyze the soft tissue profile changes in relation to hard tissue changes in both upper and lower lip and chin regions after double jaw surgery. Only horizontal changes were analyzed for which an X-Y coordinate system was used. The upper lip responded variably to the direction and amount of maxillary positioning. The predictability and the significance of changes of soft tissue in relation to hard tissue are variable as it reaches towards the nose. Conclusion: It is important for the clinician to realize that numerous factors of variability exist so that he can understand that the soft-tissue profile will sometimes deviate quite markedly from what is expected, in spite of careful planning.